Training periodization over an elite rugby sevens season: from theory to practice - Marrier, B.; Le Meur, Y.; Leduc, C.; Piscione, J.; Lacome, M.; Igarza, G.; Hausswirth, C.; Morin, J.-B.; Robineau, J. (International Journal of Sports Physiology and Performance, 2019)
Purpose: To describe the training periodization in rugby sevens players competing in the World Rugby Sevens Series during a non-Olympic season. Methods: Workload data were collected over a 33-wk period in 12 male players participating in a full competitive season. Workload was quantified using session rating of perceived exertion and global positioning system-derived data during training and competition. Self-reported well-being was assessed using a questionnaire. Each variable was analyzed weekly and through 5 mesocycles (preseason, in-season 1-4), each of which ended with competition blocks. Results: The perceived load decreased throughout the season for the full squad (-68% [26%] between preseason and final competitive block, large effect) and when unavailable players were removed from the analysis (-38% [42%], moderate). Weekly perceived load was highly variable, with a typical periodization in 4 phases during each mesocycle (regeneration, training overload, taper, and competition). During the preseason, the workload was higher during the overload training phase than during the competitive period (range: +23% to +59%, large to very large, for the distance covered above individual maximal aerobic speed and the number of accelerations). This observation no longer persisted during the season. The well-being score decreased almost certainly from in-season 3 (moderate). Conclusions: These results highlighted the apparent difficulty in maintaining high-load training periods throughout the season in players engaged on the World Rugby Sevens Series despite ~4-7 training weeks separating each competitive block. This observation was likely explained by the difficulties inherent to the World Rugby Sevens Series (risk of contact injury, calendar, and multiple long-haul travel episodes) and potentially by limited squad-rotation policies.